Cloning and characterization of a potassium-coupled amino acid transporter - Castagna, Michela (The National Academy of Sciences, 1998)
Active solute uptake in bacteria, fungi, plants, and animals is known to be mediated by cotransporters that are driven by Na(+ )or H(+ )gradients. The present work extends the Na(+ )and H(+ )dogma by including the H(+ )and K(+ )paradigm. Lepidopteran insect larvae have a high K(+ )and a low Na(+ )content, and their midgut cells lack Na(+)/K(+ )ATPase. Instead, an H(+ )translocating, vacuolar-type ATPase generates a voltage of approximately −240 mV across the apical plasma membrane of so-called goblet cells, which drives H(+ )back into the cells in exchange for K(+), resulting in net K(+) secretion into the lumen. The resulting inwardly directed K(+ )electrochemical gradient serves as a driving force for active amino acid uptake into adjacent columnar cells. By using expression cloning with Xenopus laevis oocytes, we have isolated a cDNA that encodes a K(+)-coupled amino acid transporter (KAAT1). We have cloned this protein from a larval lepidopteran midgut (Manduca sexta) cDNA library. KAAT1 is expressed in absorptive columnar cells of the midgut and in labial glands. When expressed in Xenopus oocytes, KAAT1 induced electrogenic transport of neutral amino acids but excludes α-(methylamino)isobutyric acid and charged amino acids resembling the mammalian system B. K(+), Na(+), and to a lesser extent Li(+ )were accepted as cotransported ions, but K(+ )is the principal cation, by far, in living caterpillars. Moreover, uptake was Cl(−)-dependent, and the K(+)/Na(+ )selectivity increased with hyperpolarization of oocytes, reflecting the increased K(+)/Na(+ )selectivity with hyperpolarization observed in midgut tissue. KAAT1 has 634 amino acid residues with 12 putative membrane spanning domains and shows a low level of identity with members of the Na(+ )and Cl(−)-coupled neurotransmitter transporter family.